Case Report: A Case of Eyelid Myoclonic Status With Tonic–Clonic Seizure and Literature Review - Yuan, Yujun; Yang, Fenghua; Huo, Liang; Fan, Yuying; Liu, Xueyan; Wu, Qiong; Wang, Hua (Frontiers in Pediatrics, 2021)
Eyelid myoclonus with or without absence epilepsy is a rare and usually misdiagnosed disease in the neurology department. It is an idiopathic general epileptic syndrome, the onset period is 6-8 years, and is more common in girls, which is characterized by rapid abnormal eye blinking, accompanied by upward rolling of the eye and slight backward movement of the head, with eye closure sensitivity and photosensitivity. The seizure is frequent and short, dozens or even hundreds of times a day, a small number of patients may have eyelid myoclonus status. We report a patient who visits the hospital for the first time with eyelid myoclonic problem; the patient continued to wink eyes, eye roll up, and slight backward movement of the head, accompanied by reduced consciousness, video electroencephalography (VEEG) suggest continued spike slow-wave, polyspike slow-wave, After the patients with 2Hz,4Hz,6Hz,8Hz,10Hz,12Hz, and 14Hz intermittent photic stimulation (IPS), her seizures and epileptiform discharges reduced or stop, speculated that the frequent blinking action was both manifestation and triggering factor in myoclonic eyelid seizures. 7min after giving the stimulation at 20Hz, the children developed an occipital-initiated general tonic-clonic seizure, demonstrate that after sufficient IPS stimulation, the occiput cortex became excited and initiated a brain network, leading to diffuse brain discharge and tonic-clonic seizures. At 1 hour after onset, the child developed a non-convulsive state, with reduced consciousness despite no eyelid myoclonic movements, and VEEG suggested a large number of epileptic discharges. After 10 minutes of administrating midazolam, the patient's EEG immediately became normal, and the patient regained consciousness. Therefore, this paper presents a case of a patient with eyelid myoclonus status, and records the whole course of the disease and the treatment effect, and reviews the literature accordingly.